Aspek Perlindungan Perempuan Dalam Tradisi Pemaksaan Perkawainan Di Indonesia Menurut Peraturan Perundang-Undangan - Ridho, Rosyid; Khasanah, Uswatul; Agustini, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
orced marriage is not something new, it has even become a tradition in several regions in Indonesia. So, sometimes people make this a natural thing because it is part of local customs. However, in reality, the tradition of forced marriage has the potential to cause sexual violence in the household. In this article we will discuss aspects of women's protection in the forced marriage tradition in Indonesia. Apart from that, it will also be discussed regarding how Indonesian laws and regulations view the tradition of forced comrades in Indonesia. The research method used is library research with a normative juridical approach. Based on the results of the study, it shows that forced marriage in Indonesia violates women's freedom to choose their partner. Apart from that, forced marriage is also part of sexual violence so it violates human rights and is contrary to various regulations in Indonesia. Looking at these facts, aspects of legal protection that victims of forced marriage must obtain include repressive and preventive legal protection. This repressive legal protection aims to prevent forced marriages in accordance with Indonesian laws and regulations. Meanwhile, preventive legal protection aims to resolve problems that have arisen as a result of forced marriage. This last handling of legal protection is carried out by the court in accordance with Indonesian laws and regulations.